2013
DOI: 10.1086/673143
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Contact Precautions on Patient Perception of Care and Satisfaction: A Prospective Cohort Study

Abstract: Objective Contact precautions decrease healthcare worker–patient contact and may impact patient satisfaction. To determine the association between contact precautions and patient satisfaction, we used a standardized interview for perceived issues with care. Design Prospective cohort study of inpatients, evaluated at admission and on hospital days 3, 7, and 14 (until discharged). At each point, patients underwent a standardized interview to identify perceived problems with care. After discharge, the standardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
57
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(59 citation statements)
references
References 16 publications
(37 reference statements)
1
57
0
Order By: Relevance
“…2 3 Some studies have used the HCAHPS survey to compare the hospital experience of isolated and non-isolated patients. [4][5][6] In Gasink et al, the HCAHPS survey was administered to 43 isolated and 43 non-isolated patients. The survey was performed while the patients were still in the hospital, which may have not adequately evaluated the entire hospital experience.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2 3 Some studies have used the HCAHPS survey to compare the hospital experience of isolated and non-isolated patients. [4][5][6] In Gasink et al, the HCAHPS survey was administered to 43 isolated and 43 non-isolated patients. The survey was performed while the patients were still in the hospital, which may have not adequately evaluated the entire hospital experience.…”
Section: Discussionmentioning
confidence: 99%
“…Mehrotra et al found that contact precautions were not associated with significant differences in HCAHPS scores in 88 patients. 6 In a large study from the Cleveland Clinic, isolated patients reported lower HCAHPS scores for physician communication and staff responsiveness, but the analysis did not adjust for potential confounding factors. 4 In the current study, there were no significant differences in HCAHPS scores for isolated and non-isolated patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have suggested that CP may increase patient adverse events such as falls and pressure ulcers, 6,7 isolation, and depression, 8 perhaps because healthcare workers do not spend as much time in direct patient care with patients in CP. 9,10 Facilities have reported delayed bed assignment, 11 patient perceptions of poor coordination of care, 12 and decreased healthcare worker adherence to isolation precautions with increasing numbers of patients on CP. 13 Given the availability of a bundle of interventions of which CP is just 1 component, published evidence pointing to negative impact on care, and voiced concern regarding effort vs value, we set out to determine (1) whether CP remains a widely used intervention for MRSA and VRE, (2) how facilities use CP, and (3) what other key interventions are in place to reduce the risk of transmission.…”
mentioning
confidence: 99%
“…This has the potential to reduce costs through eliminating waste from excess personal protective equipment14 and through decreasing staff time in donning personal protective equipment, and it also contributes to increased patient satisfaction. 15 The system not only tracked critical pathogens and initiated appropriate precautions, but it logged a complete history of a patient's status in harboring these organisms. All flags were pathogen specific, with start dates and discontinuation dates, if applicable, logged in the system.…”
Section: Discussionmentioning
confidence: 99%